Endobronchial ultrasound-guided cryobiopsies in peripheral pulmonary Lesions: a feasibility study - BOSTANCI, KORKUT (EUROPEAN RESPIRATORY SOC JOURNALS LTD, 2014)
Peripheral lung lesions are sometimes difficult to reach even with endobronchial ultrasound (EBUS) and insufficient material is often obtained by transbronchial forceps biopsy. Cryoprobes can be used for performing tissue biopsies. We evaluated the safety and feasibility of the cryoprobe in combination with EBUS for the diagnosis of peripheral lung lesion. Patients with peripheral lung lesions of up to 4 cm were enrolled. After identifying the lung lesion by radial EBUS, forceps biopsies and cryobiopsies were performed in a randomised order. We evaluated safety and feasibility,, and compared diagnostic yield and sample size. 39 patients were randomised and the peripheral lung lesion was reached in 31. The overall diagnostic yield was 60.5% and, in the lesions reached by EBUS, it was 74.2%. In 19 cases, the diagnosis was made with forceps as well as cryobiopsy and, in four cases, only with cryobiopsy. Cryobiopsies were significantly larger than forceps biopsies (11.17 mm(2) versus 4.69 mm(2), p<0.001). We observed one case of moderate bleeding. Transbronchial cryobiopsy with EBUS guidance is safe and useful to obtain histological samples. Larger tissue samples can be obtained by cryoprobe.
Keywords: LUNG-CANCER; DIAGNOSTIC YIELD; BIOPSY; ULTRASONOGRAPHY; SHEATH; TRIAL; INCREASES; NODULE; METAANALYSIS; MANAGEMENT